Enhancing Marine Tourism Through Halal Extension and Product Quality Development - Nihayah, Ulin; Komarudin (Universitas Islam Negeri Raden Intan Lampung, 2025)
Marine tourism has emerged as a strategic sector contributing to both economic growth and cultural exchange, yet its sustainability increasingly depends on meeting global standards of quality and inclusivity. One key aspect is the assurance of halal products, which not only reflects compliance with Islamic principles but also enhances consumer trust and broadens market access. This study explores the role of halal extension services in strengthening product quality within marine tourism ecosystems. Using a mixed-method approach involving literature analysis, field observations, and stakeholder interviews, the research highlights how halal certification, training, and community-based mentoring programs improve hygiene standards, product traceability, and service excellence. Findings indicate that halal extension acts as a catalyst in empowering local entrepreneurs, integrating ethical values into product development, and promoting resilience in coastal economies. Moreover, the study underscores the synergy between halal assurance and sustainable tourism, suggesting that a well-structured halal ecosystem can simultaneously elevate product competitiveness and support environmentally responsible practices. The results contribute to policy formulation and practical models for developing halal-based marine tourism, ensuring that the sector not only thrives economically but also aligns with cultural, spiritual, and ecological values.